2019
DOI: 10.1007/s11295-019-1374-1
|View full text |Cite
|
Sign up to set email alerts
|

Creation of an avocado unambiguous genotype SNP database for germplasm curation and as an aid to breeders

Abstract: Avocado (Persea americana) is an important tropical and subtropical fruit tree crop. Traditional tree breeding programs face the challenges of long generation times and significant expense in land and personnel resources. Avocado selection and breeding can be more efficient and less expensive through the development and application of molecular markers. A total of 1524 individuals were genotyped with 384 SNPs creating the largest SNP genotype database for avocado. These individuals correspond to four extensive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Avocado (Persea americana Mill. ), which is a member of the family Lauraceae of the order Laurales, is one of the most economically important subtropical/tropical fruit crops worldwide [1][2][3]. Avocado is a highly diverse species with local variations that have resulted in various ecological races [4].…”
Section: Introductionmentioning
confidence: 99%
“…Avocado (Persea americana Mill. ), which is a member of the family Lauraceae of the order Laurales, is one of the most economically important subtropical/tropical fruit crops worldwide [1][2][3]. Avocado is a highly diverse species with local variations that have resulted in various ecological races [4].…”
Section: Introductionmentioning
confidence: 99%
“…Previous genetic characterizations providing tangential signals of horticultural races have used targeted genes ( Chen et al, 2009 ), chloroplast DNA ( Ge et al, 2019 ), SSR ( Alcaraz and Hormaza, 2007 ; Ferrer-Pereira et al, 2017 ; Boza et al, 2018 ; Sánchez-González et al, 2020 ), and SNP markers ( Kuhn et al, 2019b ; Rubinstein et al, 2019 ; Talavera et al, 2019 ), in some cases using gene-bank accessions, such as from the Venezuelan germplasm bank—Instituto Nacional de Investigaciones Agrícolas–Centro Nacional de Investigaciones Agropecuarias ( Ferrer-Pereira et al, 2017 ), the National Germplasm Repository (United States Department of Agriculture—Agricultural Research Service Subtropical Horticultural Research Station) in Miami ( Kuhn et al, 2019a ,b), and the Spanish germplasm bank ( Talavera et al, 2019 ). Despite some of these analyses captured all three races ( Talavera et al, 2019 ), others exhibited mixed and inconclusive population structure ( Cañas-Gutiérrez et al, 2015 , 2019 ; Cañas-Gutierrez et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Another study identified 5,050 SNPs and used them to construct a high-density linkage map for avocado ( Kuhn et al, 2019b ). This allowed the authors to estimate genetic diversity in germplasm collections, determine parentage and identify mislabeled or self-pollinated individuals ( Kuhn et al, 2019a ).…”
Section: Tools For the Functional Characterization Of Avocado Defensementioning
confidence: 99%